Rules of procedure and conduct of business in the council of states : Rajya Sabha (New Delhi, 2010)
Article 118(1) of the Constitution empowers each House of Parliament to make rules for regulating its Procedure and the Conduct of its business. Under this provision of the Constitution, Rajya Sabha adopted rules for regulating its procedure and the conduct of its business on June 2, 1964. The rules were brought into force with effect from July 1, 1964.
Keywords: Legislative Rules and Procedure